«ҚЫРҚ ҚЫЗ» ДƏСТАНЫНЫҢ СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЛИЎИ ҲƏМ КӨРКЕМ АЎДАРМА МƏСЕЛЕЛЕРИ - Бекбергенова, М.Д.; Алламбергенова, Г.К. (SCIENCE and SOCIETY, 2022)
This article discusses the issues of literary translation of the Karakalpak heroic epic " Forty Girls" into the national languages of the Turkic-speaking, European peoples. The issues of preserving the artistic image of the original in translation are being studied. As well as the problems of transferring national identity, features of the national character, traditions and rituals in literary translation. The issues of the significance in are considered the literary translation of the epic "Forty Girls" for foreign literatures.